Unobserved mortality occurs early in larval walleye (Sander vitreus) aquaculture - Neibauer, Jared; Branville, Colton; Holmes, Kendall; Hauser, Emma; Firkus, Tyler (Frontiers in Aquaculture, 2024)
One of the most persistent challenges in walleye larviculture is the high rate of unobserved mortality occurring within the first 30 days post-hatch. Walleye larviculture is characterized by high mortality rates, but oftentimes, only a fraction of the total mortality in walleye larviculture is observed. Unobserved mortality is frequently attributed to a high rate of cannibalism, but decomposition of larvae and other factors may also be important contributors. Unobserved mortality can make walleye larviculture especially challenging as accurately estimating daily feed rations and forecasting larval production rely on accurate counts of surviving fish. Despite the importance of unobserved mortality, there is little empirical evidence available that assesses the temporal occurrence and causes of unobserved mortality in walleye larviculture. This study assessed when unobserved mortality occurs during walleye larviculture by examining survival at three timepoints (8, 15, and 30 days post-stocking). Tanks were cleaned daily and dead fry were enumerated to account for observed mortality. At the end of each treatment period, the tanks were drained, all remaining fry were enumerated, and the unobserved mortality rate was calculated. While observed mortality trended higher as trial duration increased, unobserved mortality did not increase significantly from the 8-day treatment suggesting that the bulk of unobserved mortality occurs during the first 8 days of walleye larviculture.